CINE TRANSNACIONAL, EL SISTEMA DE FESTIVALES Y LA TRANSFORMACIÓN DIGITAL - Thomas ELSAESSER, (Fonseca, Journal of Communication, 2023)
This paper considers the idea of transnational cinema from several different perspectives: first, as a term that competes with other terms which also want to characterize non-Hollywood cinema, such as ‘world cinema’, ‘independent cinema’, ‘accented cinema’, ‘peripheral cinema’. Despite being itself a problematic concept, transnational cinema best represents the situation of contemporary filmmaking under conditions of globalization